2022
DOI: 10.1038/s42003-022-03598-0
|View full text |Cite
|
Sign up to set email alerts
|

Nano pom-poms prepared exosomes enable highly specific cancer biomarker detection

Abstract: Extracellular vesicles (EVs), particularly nano-sized small EV exosomes, are emerging biomarker sources. However, due to heterogeneous populations secreted from diverse cell types, mapping exosome multi-omic molecular information specifically to their pathogenesis origin for cancer biomarker identification is still extraordinarily challenging. Herein, we introduced a novel 3D-structured nanographene immunomagnetic particles (NanoPoms) with unique flower pom-poms morphology and photo-click chemistry for specifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…Ultrafiltration is subject to EV destruction due to the shear force of membrane filtration. Currently, affinity purification such as immunomagnetic beads and affinity column are getting more recognition in terms of homogeneous population and purity relevant to interests [ 139 ]. Due to variance in EV isolation and variable return of results from widely accepted methods, it is important that highly specific and sensitive isolation techniques are developed in the future for improving diagnostic outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrafiltration is subject to EV destruction due to the shear force of membrane filtration. Currently, affinity purification such as immunomagnetic beads and affinity column are getting more recognition in terms of homogeneous population and purity relevant to interests [ 139 ]. Due to variance in EV isolation and variable return of results from widely accepted methods, it is important that highly specific and sensitive isolation techniques are developed in the future for improving diagnostic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For developing exosome based diagnostic test, the well-established exosome isolation and characterization are critical and need to be standardized. Some pioneer research work has been reported recently to overcome the isolation challenge and ensure the exosome purity and specificity [ 84 , 96 , 139 ]. However, clinical translation is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that compared to bare beads, 3D nanostructures produce better capture efficiencies. 48 Therefore, we expected that binding kinetics of biomarker molecules with the probes on the MB-ZnO NRs might be improved and thus fluorescence signal can be measured in the diffusion-limit condition. The intensity from the multiple fluorescence images was obtained for each MB-ZnO NRs samples over the period of incubation, and the results are shown in Figure 3e.…”
Section: Biosensing Platform Based Onmentioning
confidence: 99%
“…This label-free technique can directly quantify exosomes in serum samples and has shown diagnostic potential for prostate cancer. Additionally, the porous structure has been used to isolate exosomes with and without other isolation materials and devices [ 191 , 192 , 193 ].…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%